Characterization of a compact filament-driven multicusp ion source for low energy time-of-flight Rutherford backscattering spectrometry application - Dangtip S. (2014)
The characterization of materials by ion beam based Rutherford backscattering spectroscopy (RBS) was studied. It was found that a compact filament-driven multicusp ion source was used for the time-of-flight RBS applications. The use of beam width to deduce the beam emittance and measurement at beam profile monitor was investigated. Results shows the beam size and the beam divergence at the entrance of the quadrupole magnet.